2010
DOI: 10.1177/0892705710391621
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotube/Polysulfone Composites

Abstract: The solution method was used to create polysulfone/carbon nanotubes composites. The effect of three solvents (NMP, DMF, and THF), treatments (nitric acid and ethanol) and surfactants (ODA and OCA) on CNT/ solvent stability was investigated. NMP and DMF resulted in improved stability compared to THF, and all CNT treatments improved stability. Four composites were produced with CNT loadings of 0-5 wt%: as-received CNT and nitric acid treated in THF, as-received CNT and OCA surfactant CNT in NMP. Optical, TEM, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…CNT has tendency to form agglomerate in polymer matrix due to strong van der Waals interactions and this property limits its applications. Different methods are applied to exceed this agglomeration problem including solution mixing, 15,16 in situ polymerization, 17,18 melt mixing, 19 –21 addition of appropriate compatibiliser, 22,23 and surface modification 24,25 of CNT with appropriate surface groups to achieve better interfacial adhesion with polymer matrix. Melt mixing is one of the most useful methods especially for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…CNT has tendency to form agglomerate in polymer matrix due to strong van der Waals interactions and this property limits its applications. Different methods are applied to exceed this agglomeration problem including solution mixing, 15,16 in situ polymerization, 17,18 melt mixing, 19 –21 addition of appropriate compatibiliser, 22,23 and surface modification 24,25 of CNT with appropriate surface groups to achieve better interfacial adhesion with polymer matrix. Melt mixing is one of the most useful methods especially for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S3a in the Supporting Information compares the number of samples that overcame the steps to the total number of fabricated samples, when the Ag/MWCNT composite patterns were made with the 0.15 wt % MWCNT ink across the steps with heights of 240 and 300 μm. By observing the optical images shown in Figure S3b–d, we found that the concentration limit of MWCNT is 1 wt % because the composite pattern started to have aggregated MWCNT clusters reducing the conductivity of the patterns. , However, in the case of AgNW, it could be found that the maximum step height remained proportional to the concentration of AgNW without the clustering problem. Moreover, R s was inversely proportional to the concentration.…”
Section: Resultsmentioning
confidence: 96%
“…The performed analyzes showed an improvement of CNT stability after the modification processes, with a higher increase in NMP and DMF compared to THF. Both mechanical tests and thermal analysis confirmed the presence of a residual solvent in all samples as a plasticizer, resulting in a significant reduction in the glass transition temperature (Tg) [42]. Subsequently, symmetric polymeric membranes were obtained and characterized instead of asymmetric membranes by solvent evaporation method, using polysulfone as polymer and CNT-amino as additives.…”
Section: Synthesis Characterization and Propertiesmentioning
confidence: 88%